Why merger talks collapse: an exploratory study about contributing factors to ‘wedding cold feet' and deal making failure in mergers and acquisitions from the perspective of active deal making professionals in Brazil - Sales, Augusto Cesar Silva (2014)
Why merger talks collapse: an exploratory study about contributing factors behind ‘wedding cold feet' and deal making failure in Mergers and Acquisitions from the perspective of active deal making professionals in Brazil. One basic question encouraged this study: after all the effort, expectations and money usually invested in dealmaking, why are so many transactions simply abandoned, even when the benefits are clear for the business, shareholders, customers and employees?